Guidance for Sovereign Green Bond Issuers : With Lessons from Fiji's First Emerging Economy Sovereign Green Bond - International Finance Corporation (Washington, DC, 2018)
A sovereign green bond presents countries with an opportunity to demonstrate national leadership in the green financing agenda while giving exposure to a new investor base and solidifying a country’s commitment to complying with the Paris Climate Change Agreement. While green bonds allow sovereign issuers to appeal to a new class of investors, domestically or internationally, in addition to the usual costs associated with the preparation of a vanilla government bond, green bonds require upfront and ongoing resources that are not recoverable through bond proceeds. Many potential investors need to be educated on the benefits of a green bond, for themselves and the country. Studies have shown an increasing number of millennials are attracted to investments that will have a positive environmental impact, making it a wise choice for retail issuances and institutions whose customer base will increasingly include millennials. Clearly identifying the reasons for issuing will drive many decisions in the issuance process. If a country’s motivation to issue a green bond is prompted by a desire for cheaper financing compared to a vanilla issuance, then caution should be exercised. While it has been suggested they may have the potential to attract a pricing premiu